INTRAVENOUS VITAMIN C (IVC) TREATMENT OUTCOME OF COVID 19 PATIENTS ADMITTED IN HOSPITAL: A SYSTEMATIC REVIEW - Pratiwi, Auria Ekanti; Suwarsa, Oki; Achadiyani; Atik, Nur (Journal of Vocational Health Studies, 2023)
Background: Coronavirus disease 2019 (COVID-19) is still becoming a problem in several countries with the emergence of new variants with the latest variant named Omicron. Studies show that patients with COVID-19 tend to have Acute Respiratory Distress Syndrome (ARDS) because of high pro-inflammatory cytokines and chemokines levels. Since its role as an antiviral agent, anti-cytokine, immunomodulator, antioxidant and has potential effect in maintaining body functions, vitamin C can be used as one of therapy. There is still arguable about giving treatment of COVID-19 patients with Intravenous Vitamin C (IVC). Previous research has not been discussed related to accelerating recovery and decreasing mortality. Purpose: To identify the impact of IVC intervention given to COVID-19 patients admitted in hospital by reviewing clinical outcomes particularly on complexity or mortality. Review: Literature information was sourced from PubMed, ScienceDirect, and Google Scholar databases through keywords to retrieve inclusion criteria published during 2019-2021. Result: We found that IVC influenced inflammatory biomarkers such as CRP, d-dimer, ferritin, and several inflammatory cytokines, mortality, length of stay, oxygenation, organ and immune system function but showed no significant difference between the control group. Conclusion: IVC treatment might be an essential adjuvant therapy in the aggravation of mild, severe, and critical COVID-19 patients, but did not understate complexity or mortality. Hence, further research and evaluation in clinical trials are needed.